Age‐related increase in IL‐17 activates pro‐inflammatory signaling in prostate cells. Issue 5 (5th January 2015) - De Angulo, Alejandra; Faris, Robert; Daniel, Benjamin; Jolly, Christopher; deGraffenried, Linda
Abstract Background A close relationship between aging, inflammation, and prostate cancer is widely accepted. Aging is accompanied by a progressive increase in pro‐inflammatory cytokines, including interleukin 17 (IL‐17), a key pro‐inflammatory cytokine that becomes dysregulated with age. However, the contribution of IL‐17 to age‐related prostate tumorigenesis remains unclear. The aim of this study was to investigate the role of age‐related IL‐17 dysregulation in prostate tumorigenesis. Methods Serum and splenic T‐lymphocytes from young GPAT‐1 knock‐out aging‐mimic T cell mice as well as young and aged wild‐type mice were collected. shRNA was used to knock down the IL‐17 receptor in LNCaP prostate cancer cells and RWPE‐1 non‐transformed prostate epithelial cells, which were then exposed to the mouse sera or conditioned media from stimulated T‐lymphocytes. NF‐κB activation, NF‐κB target gene expression, and cell proliferation were all measured in these cells by luciferase assay, qPCR, Western blot analysis, and MTT assay, respectively. Results T‐lymphocyte‐secreted IL‐17 from aging‐mimic mice induced NF‐κB activity and target gene expression in LNCaP and RWPE‐1 cells. It also promoted proliferation of these cells. Conclusion Aging‐mimic T cell mice produce increased levels of IL‐17, which stimulates the pro‐inflammatory NF‐κB pathway in prostate epithelial cells. NF‐κB increases inflammation, carcinogenesis and metastatic potential in the prostate. These findings provide evidence that the dysregulation of cytokine production seen in aged T cells may directly contribute to the increased risk for prostate cancer in the elderly. Prostate 75: 449–462, 2015. © 2015 Wiley Periodicals, Inc.